Theoretical aspects of the modern informational society - Sauyrbaeva Ә.Ж.; Gavra Д.П. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The scientific article examines the features of the development of mass media in the Internet space of Kazakhstan and the formation of an information society. Theoretical approaches to analyzing the processes of information society formation are systematized, and the tasks and main directions of mediation are defined. In addition, to date, the state of use of information technologies on the Internet in the media has been analyzed, which has caused feedback, through the dynamics of Internet users and electronic media. Thus, the development of modern information and communication technologies was considered as a factor in the formation of the paradigm of the network information society. As a result, the activity of electronic mass media was recognized in the media system. The topic raises the importance of directing the new media system to ensure the potential, renewal, and development of the information society.